2005
DOI: 10.1016/j.cca.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of the antioxidant system in erythrocytes of trained adult rats: Impact of intermittent hypobaric-hypoxia at two altitudes

Abstract: We have investigated the effects of daily exposure to intermittent hypobaric-hypoxia to two simulated altitudes (5700 m and 6300 m) in adult male rats that had been regularly swim trained in normoxia at sea level prior to exposures. Superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) along with the oxidative stress (OS) indices, malondialdehyde (MDA) and protein carbonyl content were measured in erythrocytes and their membranes. Hemoglobin increased in the trained animals exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Oxidation of proteins by free radicals plays a major role in many oxidative processes within the cells, the magnitude of which is often measured by the carbonyl content (Hawkins and Davies 2001). Oxidative modification of proteins, considering their multiple functions, unlike LPO, can be selective and specific (Adams et al 2001). It is worth noting that membrane proteins are the major targets of postbiosynthetic alterations during erythrocyte intravascular aging, a situation similar to OS, wherein increased generation of free radicals occur (Gallagher et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidation of proteins by free radicals plays a major role in many oxidative processes within the cells, the magnitude of which is often measured by the carbonyl content (Hawkins and Davies 2001). Oxidative modification of proteins, considering their multiple functions, unlike LPO, can be selective and specific (Adams et al 2001). It is worth noting that membrane proteins are the major targets of postbiosynthetic alterations during erythrocyte intravascular aging, a situation similar to OS, wherein increased generation of free radicals occur (Gallagher et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The latter two form a substantial defense network against oxidative stress imposed by several other factors such as physical exercise (Asha et al 2005;Cooper et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was drawn as previously reported (Asha et al , 2005 from the heart into 10% EDTAcoated tubes and erythrocytes were separated by the method of Dodge et al (1963). Blood was drawn as previously reported (Asha et al , 2005 from the heart into 10% EDTAcoated tubes and erythrocytes were separated by the method of Dodge et al (1963).…”
Section: Blood Samplingmentioning
confidence: 99%
“…It has also been found that erythrocytes equilibrated at low pH show increased phagocytosis since acidification of RBC increases the interaction with monocytes (Biondi et al 2002). Our earlier studies on in vivo (Asha Devi et al 2005) and in vitro models (Vani et al 2010;Shiva Shankar Reddy et al 2007) of oxidative stress in rat erythrocytes have demonstrated the beneficial effects of using antioxidants, vitamin E and C in preventing stress-induced injury. It is clear therefore that a considerable interaction exists between antioxidant system and oxidative damage to membrane proteins and lipids in mammalian erythrocytes treated with 2, 2 0 -azobis (2-aminidinopropane) dihydrochloride (AAPH), a water-soluble peroxyl radical initiator (Asha Zou et al 2001).…”
Section: Introductionmentioning
confidence: 92%